A Concept Analysis of Quality Assurance and Quality Enhancement in Higher Education Institutions - Mkhize, Thandeka; Cassimjee, Rabia (South African Journal of Higher Education, 2016)
As a relatively new concept, there is a need for quality enhancement to be analysed in the South African higher education context. Traditionally, quality in higher education has always placed an emphasis on quality assurance. This has led to the perception by academics that when measuring performance and quality they just need to comply with the bureaucratic requirements as prescribed by quality standards and criteria. However, if higher education is to benefit from the implementation of quality assurance processes, the emphasis must not be on compliance but rather on enhancement. This paper critiques quality enhancement using the Concept Analysis Model. Concept analysis is essential because concepts are the building blocks from which theories can be built concept. Secondly, analysis is necessary if the concept is to be operationalised. This allows researchers to specify what will result from of implementing the concept. When the definition or attributes of a concept are not clear, the ability of the concept to assist in fundamental tasks is greatly impaired. Clarifying quality enhancement will enable higher education institutions and academics to put mechanisms and strategies in place to implement quality enhancement processes. In turn, this will produce a more positive perception of quality by academics.